Ethical leadership in modern employment relations: Lessons from St. Benedict - Chan, C.; McBey, K.; Scott-Ladd, Brenda (Springer Netherlands, 2011)
Business ethics and leadership play an increasingly important role for contemporary organizations as employers and employees search for new ways to cope with ongoing changes in organizational environments. Research attention to date has focused upon how to improve process and structural configurations, while there has been scant attention devoted to an examination of the ethical and leadership perspective. This article breaks new ground by exploring the applicability of the Rule of St. Benedict (RSB) to modern employment relationships. A significant proportion of the RSB is directly relevant for today’s leaders, as it contains crucial lessons dealing with leadership issues such as ethics, cultivating a consultative climate, encouraging the virtues of humility, obedience (‘‘servant’’ leadership), justice, discretion, prudence, discernment, and personnel-related issues such as discipline and termination.